The road - McCarthy, Cormac (Alfred A. Knopf, 2006)
The Road is the profoundly moving story of a journey. It boldly imagines a future in which no hope remains, but in which the father and his son, "each the other's world entire," are sustained by love. Awesome in the totality of its vision, it is an unflinching meditation on the worst and the best that we are capable of: ultimate destructiveness, desperate tenacity, and the tenderness that keeps two people alive in the face of total devastation.